The SAME-TT2R2 score predicts the quality of anticoagulation control in patients with acute VTE - Palareti, Gualtiero; Antonucci, Emilia; Lip, Gregory Y. H.; Testa, Sophie; Guazzaloca, Giuliana; Falanga, Anna; Pengo, Vittorio; Poli, Daniela; for the START-Register Participants (Thrombosis and Haemostasis, 2016)
The SAMe-TT2R2 score has recently been proposed to predict the quality of vitamin K antagonist (VKA) anticoagulation control in patients with atrial fibrillation. We aimed at investigating whether the score is effective also in patients with venous thromboembolism (VTE). Patients included in the START-Register because started VKA therapy for a recent VTE episode and with > 3 months follow-up were analyzed. The score was calculated using the baseline patient’s characteristics present in the electronic database of the registry, where all INR results were also available and analysed to calculate the time in therapeutic range (TTR). A total of 1308 patients (53.4 % female, median age 68 years) were analysed. During 998 patient-years followup, the median TTR was 63 %. The maximum score in the patients was 4, with 70 % of them having 0–1. INR controls within range (2.0–3.0) were significantly less prevalent in patients with score ≥ 2 vs 0–1 score (58.5 ± 20 % vs 61.5 ± 19 %, respectively, p = 0.046). Patients with score ≥ 2 vs 0–1 had a highly significant lower TTR during the first 3 months of therapy (53 ± 26 % and 61 ± 26 %, respectively; p=0.0001), difference mainly due to more time spent below 2.0 INR (38 ± 28 % vs 31.3 ± 26.7 %, respectively; p=0.0001). In conclusion, the study proved, for the first time, that the SAMe-TT2R2 score is useful to predict among VTE patients those who will have good (score 0–1) or less good (score ≥ 2) VKA anticoagulation control. The score can help decision-making in everyday clinical practice, especially when choosing between VKA and non-vitamin K antagonists direct anticoagulants.Note: The review process for this paper was fully handled by Christian Weber, Editor in Chief.
Keywords: Anticoagulants; quality control; warfarin; SAMe-TT2R2 score